Enterobacter hormaechie: An Etiological Agent for Bovine Mastitis Identified through PCR and Sequencing - Dubey, Sanjay Kumar; Kumar , Praveen; Kumari, Nandani; Rajak, S.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Mastitis is an important disease at the global level. With the steep rise in cases of bovine mastitis, it has become a matter of concern. It is responsible for nearly 70 per cent of the losses in milk production in India and also poses a significant public health risk. Diagnostic methods in field conditions are rather too crude, relying mainly on the apparent symptoms. Diagnostic kits available for field conditions for mastitis fail to give accurate indications about the causative agents, thus increasing antibiotic resistance. Although, molecular methods are not economical, they are reliable diagnostic tool for early and accurate assessment of etiological agents. Current study deals with the usage of PCR-based diagnostic method coupled with sequencing to find out the causative agent for mastitis in milk sample. In the present study, presence of Enterobacter hormaechie (E. hormaechie), was confirmed using PCR method. Sequencing was used to find the base sequence and phylogenetic tree of the causative agent. The 16S rRNA gene-based DNA Barcoding of the bacteria found in milk revealed that cattle are infected with E. hormaechei bacteria. The presence of E. hormaechie is also a matter of concern due to public health importance. More research should be done in future with greater number of samples for prevalence of microorganisms from the same region.